THE WRATH OF NOESANGKARA, A LOCAL ROLE-PLAYING TABLETOP GAME PROJECT - Wulandari, Rachmaghita Sribhuwana; Siswanto, Riky Azharyandi; Aditya, Dimas Krisna (eProceedings of Art & Design, 2023)
The Wrath of Noesangkara is an Indonesian-themed fantasy tabletoproleplaying game that teaches students about Indonesian culture while also providing anew way to play teamwork without worrying about toxic traits. The game is designed toallow players to achieve the main goal by cooperating while exploring and learningabout traditional weapons and spells, as well as fighting creatures from Indonesianlegends and myths. Boardgames have a long history of bringing up moral ideas from thepast, and they have evolved into a medium for learning through play. It is an excellentplatform for engaging and enjoyable learning of Indonesian culture.Keywords: Indonesian culture, tabletop role-playing game, college students, The Wrathof Noesangkara